Female‐biased sex allocation and lack of inbreeding avoidance in Cubitermes termites. Issue 10 (31st March 2021) - Sinotte, Veronica M.; Conlon, Benjamin H.; Seibel, Elena; Schwitalla, Jan W.; de Beer, Z. Wilhelm; Poulsen, Michael; Bos, Nick
Abstract: Sexually reproducing organisms face a strong selective pressure to find a mate and ensure reproduction. An important criterion during mate‐selection is to avoid closely related individuals and subsequent potential fitness costs of resulting inbred offspring. Inbreeding avoidance can be active through kin recognition during mate choice, or passive through differential male and female‐biased sex ratios, which effectively prevents sib‐mating. In addition, sex allocation, or the resources allotted to male and female offspring, can impact mating and reproductive success. Here, we investigate mate choice, sex ratios, and sex allocation in dispersing reproductives (alates) from colonies of the termite Cubitermes tenuiceps . Termites have a short time to select a mate for life, which should intensify any fitness consequences of inbreeding. However, alates did not actively avoid inbreeding through mate choice via kin recognition based on genetic or environmental cues. Furthermore, the majority of colonies exhibited a female‐biased sex ratio, and none exhibited a male‐bias, indicating that differential bias does not reduce inbreeding. Sex allocation was generally female‐biased, as females also were heavier, but the potential fitness effect of this costly strategy remains unclear. The bacterium Wolbachia, known in other insects to parasitically distort sex allocation toward females, was present within all alates. While Wolbachia is commonly associated with termites, parasitism has yet to be demonstrated, warranting further study of the nature of the symbiosis. Both the apparent lack of inbreeding avoidance and potential maladaptive sex allocation implies possible negative effects on mating and fitness. Abstract : Cubitermes termites do not appear to avoid inbreeding through mate choice. Furthermore, investigated colonies generally had a female bias, and never a male bias, indicating the termites also do not avoid inbreeding through split sex ratios. Lastly, all investigated sexuals were infected with Wolbachia, which is transmitted only through females. This raises the possibility that this symbiont selfishly influences the termites' sex ratio.